Relación entre la inteligencia emocional y conductas de riesgo en adolescentes de dos escuelas públicas de Lima Metropolitana - Lelkes Rizo Patrón, Kiara (2019)
Each year, the numbers of adolescents who begin to participate in risk behaviors at an early age are increased. That is why, the purpose of this research is to determine whether there is a relationship between the components of emotional intelligence and risk behaviors, in adolescents between third and fifth year of high school in Metropolitan Lima. The sample consisted of 153 students (Mage= 15.14, SD=1.13, 46.9% men) selected by non-probabilistic sampling. The inventory of the Emotional Quotient of BarOn ICE and the Confidential Questionnaire of Risk Behaviors were applied. It could be concluded that there is a negative relationship between the interpersonal component and the risk behaviors of tobacco consumption, alcohol consumption and sexual relations. Regarding the intrapersonal component, there was a negative relationship with the age of onset of tobacco use, but a direct relationship with the risk behaviors of tobacco consumption, alcohol consumption, sexual relations and tobacco use of best friends; that is, with greater awareness and expression of one´s emotions, there are more relationships with friends who maintain risky behaviors. Finally, regarding the stress management component, an inverse relationship with respect to alcohol consumption and sexual relations of best friends could be evidenced; this indicates that the better the stress management, the less relationships with peers that present those risk behaviors. However, a more positive relationship with the risk behaviors of tobacco use by best friends, age of onset of tobacco use, frequency of alcohol consumption and age of onset of sexual relations. This research could help the educational centers of Peru give greater importance to the development of students emotional intelligence since they were young, as it could be an important factor for the prevention of the appearance of risk behaviors in adolescents.